Time to vote? - John Gibson; Bonggeun Kim; Steven Stillman; Geua Boe-Gibson (Institute for the Study of Labor (IZA), 2011)
Despite the centrality of voting costs to the paradox of voting, little effort has been made to accurately measure these costs outside of a few spatially limited case studies. In this paper, we apply Geographic Information Systems (GIS) tools to validated national election survey data from New Zealand. We calculate distance and travel time by road from the place of residence to the nearest polling place and combine our time estimate with imputed wages for all sample members. Using this new measure of the opportunity cost of voting to predict turnout at the individual level, we find that small increases in the opportunity costs of time can have large effects in reducing voter turnout.
urn:nbn:de:101:1-201107283796
Keywords: D7; R4; 330; opportunity cost; paradox of voting; travel time